What`s in a sport class? The classification experiences of paraswimmers - Van Dornick, K.; Spencer, N. L. (Adapted Physical Activity Quarterly, 2023)
The purpose of this study was to examine the classification experiences (perspectives and reflections) of paraswimmers. Classification provides a structure for parasport, with the goal of reducing the impact of impairment on the outcome of competition. Guided by interpretive description, nine paraswimmers ranging in swimming experience and sport class were interviewed. Reflective notes were also collected. Transcribed interviews were analyzed inductively, followed by a deductive analysis using Nordenfelt`s dignity framework. Three themes represent the findings: access, diversity, and (un)certainty. Despite several positive experiences, paraswimmers also discussed inconsistencies in the process leading them to question competition fairness and classification accuracy. These findings suggest that continued efforts to improve the classification system are required. In addition, paraswimmers and their allies (e.g., coaches) require more information about the classification process to better understand the outcomes and to effectively advocate for their needs.